Modified PPP Procedure in Teaching Conditional Sentences Through Whatsapp for Vocational School Students - Umi Ma'rifah; Patuan Raja; Flora Flora (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The aims of the study are to find out whether there is a significant difference in students' achievement of conditional sentences between those who are taught using modified PPP procedure through WhatsApp and those who are taught using original PPP procedure in limited offline learning. The population was the students of SMKN 1 Metro. This study is quasi-experimental, and the sampling was taken in two classes. The experimental class was given the treatment using a modified PPP procedure through WhatsApp. In contrast, the control class was given the treatment using the original PPP procedure in limited offline learning. The findings showed a significant difference in students' achievement of conditional sentences between those two procedures, which is in line with the difference in students' perception of the learning process between those two classes. Modified one was more effective in improving students' achievement of conditional sentences, especially in pandemic Covid 19, where online learning is necessary. The conclusion is that the modification of the PPP procedure through WhatsApp is very effective to use even after the pandemic, because there are more opportunities for students to discuss using WhatsApp which makes them gain a deeper understanding and better achievement of the conditional sentence material.